Risk Factor for Intraoperative Awareness - Nunes, Rogean Rodrigues; Porto, Victor Camarão; Miranda, Vivianne Trevia; de Andrade, Nayanna Quezado; Carneiro, Lara Moreira Mendes (Revista brasileira de anestesiologia, 2012)
The intraoperative awareness is an adverse event in the general anesthesia, and may occur in approximately 20,000 cases per year, which justifies the study of the risk factors for this event. The objective of this study was to review this subject in order to reduce the incidence of intraoperative awareness and psychological sequelae incurring from this incident, which may result in post-traumatic stress disorder with negative repercussions on the surgical patient social, psychic and functional development. It was conducted a review of the intraoperative awareness assessing its different phases during general anesthesia such as dreaming, wakefulness, explicit and implicit memory, as well as the analysis, consequences and prevention of its main related factors. The reduction of awareness incidence during anesthesia is related to the anesthesiologist improved scientific and technical performance, involving issues such as monitoring, comprehension of the anesthesia activity components, hypnotic and analgesic drugs, neuromuscular blocking agents, autonomic and motor reflex control, in addition to the risk factors involved in this event. O despertar intraoperatório, evento adverso na anestesia geral, pode ocorrer em cerca de 20.000 casos por ano, o que em si justifica o estudo dos fatores de risco deste evento. O objetivo deste estudo foi fazer uma revisão sobre o tema com a finalidade de diminuir a incidência do despertar intraoperatório e das sequelas psicológicas decorrentes deste incidente, que podem resultar em síndrome de estresse pós-traumático com repercussões negativas sobre o desempenho social, psíquico e funcional do paciente cirúrgico. Foi realizada revisão sobre o despertar intraoperatório, avaliando suas diferentes fases durante anestesia geral, sonhos, vigília, memória explicita e implícita, assim como análise, consequências e prevenção dos principais fatores relacionados ao mesmo. A diminuição na incidência do despertar durante anestesia está ligada ao melhor desempenho cientifico e técnico do anestesiologista, envolvendo questões como a monitoração, a compreensão sobre os componentes da atividade anestésica, drogas hipnóticas, analgésicas, bloqueadores neuromusculares, controle de reflexos autonômicos e motores, além dos fatores de risco envolvidos neste evento. El despertar intraoperatorio, que es un evento adverso en la anestesia general, puede ocurrir en aproximadamente 20.000 casos por año, justificando, por lo tanto, el estudio de sus factores de riesgo. El objetivo de este estudio, fue hacer una revisión sobre el tema, con la finalidad de disminuir la incidencia del despertar intraoperatorio y de las secuelas psicológicas provenientes de ese incidente que pueden resultar en el síndrome de estrés postraumático con repercusiones negativas sobre el desempeño social, psíquico y funcional del paciente quirúrgico. Se hizo una revisión del despertar intraoperatorio evaluando sus diferentes fases durante la anestesia general, como el sueño, la vigilia, la memoria explicita e implícita, y también el análisis, las consecuencias y la prevención de los principales factores relacionados con el despertar. La reducción en la incidencia del despertar durante la anestesia, está vinculada al mejor desempeño científico y técnico del anestesiólogo, involucrando cuestiones como la monitorización, la comprensión sobre los componentes de la actividad anestésica, fármacos hipnóticos, analgésicos, bloqueantes neuromusculares, control de reflejos autonómicos y motores, además de los factores de riesgo involucrados en este evento.